2020
DOI: 10.1111/jan.14642
|View full text |Cite
|
Sign up to set email alerts
|

The threat of COVID‐19 and its influence on nursing staff burnout

Abstract: Aims: To evaluate whether the perceived threat of COVID-19 moderates the influence of work resources and demands on burnout. Design: A cross-sectional study. Methods: We used a convenience sample of 771 nurses working in 10 hospitals in northern Spain. The data on burnout, demand, and resources at work and the perceived threat of COVID-19 were compiled in the second fortnight of April 2020 using an online questionnaire. We used several hierarchical linear regression models. Results: Work overload, material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
196
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(219 citation statements)
references
References 49 publications
12
196
1
10
Order By: Relevance
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Main characteristics of the 14 studies included in our systematic review are shown in Table 1. Study population included only nurses in five studies, 27,28,33,36,40 while nine studies [29][30][31][32]34,35,[37][38][39] included HCWs in general. A total of 17,390 nurses were included in this systematic review, while two studies 37,38 did not report the number of nurses.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations